2014
DOI: 10.3389/fncel.2014.00369
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal fluid biochemical studies in patients with Parkinson's disease: toward a potential search for biomarkers for this disease

Abstract: The blood-brain barrier supplies brain tissues with nutrients and filters certain compounds from the brain back to the bloodstream. In several neurodegenerative diseases, including Parkinson's disease (PD), there are disruptions of the blood-brain barrier. Cerebrospinal fluid (CSF) has been widely investigated in PD and in other parkinsonian syndromes with the aim of establishing useful biomarkers for an accurate differential diagnosis among these syndromes. This review article summarizes the studies reported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
57
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(62 citation statements)
references
References 318 publications
(445 reference statements)
4
57
1
Order By: Relevance
“…As CSF proteins may mirror the pathological processes in the PD brain, proteins involved in oxidative stress, inflammation, and protein aggregation—including α‐synuclein, amyloid‐beta, and (phospho)tau—as well as neurotransmitters in the CSF have been proposed as diagnostic biomarkers for PD . Several research groups have investigated the potential of lysosomal hydrolases as diagnostic biomarkers for AD and PD.…”
Section: Csf Lysosomal Enzymes As Diagnostic Biomarkers For Pdmentioning
confidence: 99%
“…As CSF proteins may mirror the pathological processes in the PD brain, proteins involved in oxidative stress, inflammation, and protein aggregation—including α‐synuclein, amyloid‐beta, and (phospho)tau—as well as neurotransmitters in the CSF have been proposed as diagnostic biomarkers for PD . Several research groups have investigated the potential of lysosomal hydrolases as diagnostic biomarkers for AD and PD.…”
Section: Csf Lysosomal Enzymes As Diagnostic Biomarkers For Pdmentioning
confidence: 99%
“…Spectral domain optical coherence tomography is currently being applied to various CNS neurodegenerative diseases [10] by measuring retinal nerve fibre layer loss and has been demonstrated to show nerve fiber anomalies in AD [11–14]. However, the method may lack specificity, as nerve fiber alterations are also observed in glaucoma, MCI [13], and Parkinson's disease [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…70 Regarding α-syn, the majority of recent studies have shown decreased CSF levels in PD patients, as compared to controls, although this marker apparently cannot distinguish among different synucleopathies. [71][72][73] In addition, levels of CSF tau protein were higher in PD patients, in particular in the early phases, as compared to controls. 74 Among other CSF biomarkers, DJ-1 levels were found to increase in early PD patients compared to controls.…”
Section: Csf Biomarkersmentioning
confidence: 97%
“…71,128,129 In a secondary analysis of the DATATOP study, lower baseline CSF α-syn levels predicted a better preservation of cognitive functions in early PD patients after 8-year-follow-up. 72 Another analysis of the DATATOP study found an association between higher phosphorylated-tau protein and greater decline in cognitive functions but slower motor progression. 130,131 Thus, it is clear that the role of tau protein is largely unknown, and, so far there are only association studies, not providing possible explanations on the importance of tau species in PD pathogenesis.…”
Section: Csf Biomarkersmentioning
confidence: 99%